A Novel Cleavage Pattern of Complement C5 Induced by Chlamydia trachomatis Infection via the Chlamydial Protease CPAF - Peng, Liang; Gao, Jingping; Hu, Zihao; Zhang, Hongbo; Tang, Lingli; Wang, Fuyan; Cui, Lei; Liu, Shanshan; Zhao, Yujie; Xu, Hong; Su, Xin; Feng, Xiaojing; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Urogenital Chlamydia trachomatis infection is one of the most common bacterial sexually transmitted diseases globally. Untreated C. trachomatis infections can ascend to the upper genital tract and establish a series of severe complications. Previous studies using C3−/− and C5−/− mice models demonstrated that C3-independent activation of C5 occurred during C. trachomatis infection. However, the mechanism of how chlamydial infection activates C5 in the absence of C3 has yet to be elucidated. To delineate interactions between C5 and chlamydial infection, cleavage products in a co-incubation system containing purified human C5 and C. trachomatis-HeLa229 cell lysates were analyzed, and a novel cleavage pattern of C5 activation induced by C. trachomatis infection was identified. C5 was cleaved efficiently at the previously unidentified site K970, but was cleaved poorly at site R751. C5b was modified to C5bCt, which later formed C5bCt-9, which had enhanced lytic ability compared with C5b-9. The chlamydial serine protease CPAF contributed to C3-independent C5 activation during C. trachomatis infection. Nafamostat mesylate, a serine protease inhibitor with a good safety profile, had a strong inhibitory effect on C5 activation induced by chlamydial infection. These discoveries reveal the mechanism of C3-independent C5 activation induced by chlamydial infection, and furthermore provide a potential therapeutic target and drug for preventing tubal fibrosis caused by chlamydial infection.